Norepinephrine Transporter Imaging in the Brain of a Rat Model of Depression Using Radioiodinated (2S, αS)-2-(α-(2-iodophenoxy)benzyl)morpholine - Naoki Kanegawa; Yasushi Kiyono; Taku Sugitaa; Yuji Kuge; Yasushisa Fujibayasi; Hideo Saji (Molecular Imaging)
To visualize the norepinephrine transporters (NETs) in various brain diseases, we developed radioiodinated (2S,αS)-2-(α-(2-iodophenoxy)benzyl)morpholine ((S,S)-IPBM). This radioligand achieved the basic requirements for NET imaging. In this study, we assessed the potential of radioiodinated (S,S)-IPBM as an imaging biomarker of NET to obtain diagnostic information about depression in relation to NET expression in the brain using a rat depression model. The ex vivo autoradiographic experiments using the (S,S)-[ 125 I]IPBM showed significantly lower accumulation of radioactivity in the locus coeruleus (LC) and the anteroventricular thalamic nucleus (AVTN) of the depression group than in those of the control group. Consequently, in vitro autoradiographic experiments showed that NET maximum binding (B max ) values in the LC and AVTN, known as NET-rich regions, were significantly decreased in the rat model of depression when compared to those of the control rats. In addition, there was an extremely good correlation between NET B max and (S,S)-IPBM accumulation ( r = .98), an indication of radioiodinated IPBM as a quantitative NET imaging biomarker. The reduction in(S,S)-[ 125 I]IPBM accumulation in the rat model of depression correlated with that of NET density. These results suggest that (S,S)-[ 123 I]IPBM has potential as an imaging biomarker of NET to obtain diagnostic information about major depression.